2023
DOI: 10.1097/bs9.0000000000000149
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1: expression regulation

Abstract: Programmed death-ligand 1 (PD-L1), expressed on the surface of tumor cells, can bind to programmed cell death-1 (PD-1) on T cells. The interaction of PD-1 and PD-L1 can inhibit T-cell responses by decreasing T-cell activity and accelerating their apoptosis. Various cancers express high levels of PD-L1 and exploit PD-L1/PD-1 signaling to evade T-cell immunity, and immunotherapies targeting the PD-1/PD-L1 axis have been shown to exert remarkable anti-tumor effects; however, not all tumor patients benefit from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 243 publications
0
10
0
2
Order By: Relevance
“…We also found that CTL infiltration in the SHMT2 low-expression group suggested a good prognosis, whereas CTL infiltration in the SHMT2 high-expression group suggested a poor prognosis, suggesting that SHMT2 is associated with T cell depletion. Several studies have reported that SHMT2 is significantly and positively correlated with PD-L1 expression (Wu et al 2019 ; Zhou et al 2023b ). PD-L1 inhibits T cell responses by activating the downstream signaling pathway of the PD-1 receptor, reducing T cell activity and promoting apoptosis, thereby inhibiting T cell responses and leading to tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that CTL infiltration in the SHMT2 low-expression group suggested a good prognosis, whereas CTL infiltration in the SHMT2 high-expression group suggested a poor prognosis, suggesting that SHMT2 is associated with T cell depletion. Several studies have reported that SHMT2 is significantly and positively correlated with PD-L1 expression (Wu et al 2019 ; Zhou et al 2023b ). PD-L1 inhibits T cell responses by activating the downstream signaling pathway of the PD-1 receptor, reducing T cell activity and promoting apoptosis, thereby inhibiting T cell responses and leading to tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the fact that PD-L1 expression correlates with disease stage and prognosis in some tumoral contexts, among which lung adenocarcinoma, nasopharyngeal carcinoma and non-small cell lung cancer ( Nie et al, 2021 ; Zhou et al, 2023 ), the relationship between surface PD-L1 and disease parameters remains largely unknown. Here we demonstrated that leukemic cells from U-CLL patients, that develop aggressive forms of the disease ( Kipps et al, 2017 ), as well as from Eμ-TCL1 mice with overt leukemia, express the highest surface amounts of PD-L1 and harbor the most relevant IS-suppressive activity.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic aberrations, such as ionizing radiation-induced double strand breaks, have been implicated in PD-L1 overexpression in cancer cells ( Zhou et al, 2023 ). Moreover, pro-inflammatory stimuli such as interferons, as well as altered oncogenic signaling pathways, among which the Ras/mitogen activated protein kinase (MAPK) and the Phosphatidyl inositol-3-kinase (PI3K)/Akt pathways, also promote PD-L1 overexpression ( Zhou et al, 2023 ). Interestingly, a complex interplay between intracellular ROS and PD-L1 expression in cancer cells has recently come to light ( Bailly, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the PD-1/PD-L1 pathway has an important role in the generation of an immunosuppressive microenvironment in tumors, there has been a significant interest in examining the regulation mechanisms underpinning the expression of the PD-L1 protein [ 43 , 87 , 88 ]. It seems that there exists a complex network of regulatory processes from epigenetic to post-transcriptional mechanisms which not only control the expression level of PD-L1 but also the resistance to the PD-1/PD-L1 blocking therapies.…”
Section: The Aging-associated Signaling Stimulates the Expression Of ...mentioning
confidence: 99%